PENGARUH KUALITAS PRODUK TERHADAP CITRA PERUSAHAAN DAN KEPUASAN SERTA DAMPAKNYA PADA KEPERCAYAAN KONSUMEN MOBIL TOYOTA AVANZA DI KOTA PALU - Sarifuddin T, Sarifuddin T (Katalogis, 2017)
This research is aimed to determine and analyze; 1) the inpluence of product quality on company’s image of Toyota Avanza in Palu ; 2) the inpluence of product quality on customer satisfaction toward of Toyota Avanza in Palu; 3) the inpluence of company’s image on customer satisfaction towards of Toyota Avanza in Palu; 4) the inpluence of satisfaction on customer trusts to Toyota Avanza in Palu. The research method is causal-descriptive with 240 samples. By using Structure Equation Modelling (SEM). the results show that; 1) product quality significantly and positively has effects on company image of Toyota Avanza in Palu; 2) product quality significantly and positively has effects on customer satisfaction toward of Toyota Avanza in Palu; 3) company’s image significantly and positively has effects on customer satisfaction towards Toyota Avanza in Palu; 4) satisfaction significanlty and positively has effects on customer trust towards Toyota Avanza in Palu.